2021
DOI: 10.1039/d1na00059d
|View full text |Cite
|
Sign up to set email alerts
|

Emerging indocyanine green-integrated nanocarriers for multimodal cancer therapy: a review

Abstract: Nanotechnology is a branch of science dealing with the developing processes of a new type of nanomaterials by several methods. In the biomedical field, nanotechnology is widely used in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 151 publications
(237 reference statements)
0
35
0
Order By: Relevance
“…10,11 With regard to phototherapeutics, ICG nanoparticles have been investigated for photothermal therapy, 26,27 photodynamic therapy, 12,81 and light-triggered drug release. 10,11 There is literature evidence that the geometric location of a photosensitizer relative to a liposome membrane (i.e., photosensitizer embedded in the membrane or protruding into the aqueous solution) can affect the rate and extent of light-triggered liposome leakage, 82 and we were curious to learn if ICG transfer to albumin would diminish the extent of NIR light-activated membrane disruption and subsequent content leakage. Therefore, we conducted experiments that measured the NIR light-triggered leakage of aqueous contents from 1,2-dipalmitoyl-sn-glycero-3phosphocholine (DPPC) liposomes that also contained ICG as the light-absorbing trigger.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10,11 With regard to phototherapeutics, ICG nanoparticles have been investigated for photothermal therapy, 26,27 photodynamic therapy, 12,81 and light-triggered drug release. 10,11 There is literature evidence that the geometric location of a photosensitizer relative to a liposome membrane (i.e., photosensitizer embedded in the membrane or protruding into the aqueous solution) can affect the rate and extent of light-triggered liposome leakage, 82 and we were curious to learn if ICG transfer to albumin would diminish the extent of NIR light-activated membrane disruption and subsequent content leakage. Therefore, we conducted experiments that measured the NIR light-triggered leakage of aqueous contents from 1,2-dipalmitoyl-sn-glycero-3phosphocholine (DPPC) liposomes that also contained ICG as the light-absorbing trigger.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although this study focused on ICG liposomes, we note that ICG transfer to albumin has been observed for a related solid nanoparticle formulation and is thus likely to occur with many types of nanoscale ICG formulations. , With regard to phototherapeutics, ICG nanoparticles have been investigated for photothermal therapy, , photodynamic therapy, , and light-triggered drug release. , There is literature evidence that the geometric location of a photosensitizer relative to a liposome membrane (i.e., photosensitizer embedded in the membrane or protruding into the aqueous solution) can affect the rate and extent of light-triggered liposome leakage, and we were curious to learn if ICG transfer to albumin would diminish the extent of NIR light-activated membrane disruption and subsequent content leakage. Therefore, we conducted experiments that measured the NIR light-triggered leakage of aqueous contents from 1,2-dipalmitoyl- sn -glycero-3-phosphocholine (DPPC) liposomes that also contained ICG as the light-absorbing trigger. ,,,,, DPPC liposomes are thermally responsive, and they leak when heated close to their transition temperature of ∼41 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations